Semiotics Study Of The 2019 Jawa Pos Political Cartoon - I Wayan Nuriarta; Ni Wayan Masyuni Sujayanthi (Institut Seni Indonesia Denpasar, 2020)
The general purpose of this study is to increase knowledge in the form of academic studies of the 2019 Jawa Pos newspaper political cartoon, and its specific purpose is to describe the denotation, connotation, myth and visual ideology of the Sunday edition of the Jawa Pos newspaper political cartoon in the sketch rubric. This study used a qualitative design. Everything related to the 2019 Jawa Pos newspaper political cartoon will be described qualitatively. The qualitative step taken was to collect, filter and analyze data to produce descriptive data in the form of words and notes related to its meaning. The research sample is the political cartoon of the January 13 and March 10 2019 edition of the Jawa Pos Newspaper. The results showed that visually, politicians occupy the top position in the drawing room. The size of the depiction was made much larger than that of the other public figures. Meanwhile, voter community figures were depicted as occupying a space position at the bottom. The depiction only showed half of the body, namely from the head to the waist. The meaning that is born from each image is determined in part by the meanings of other texts which appear to be the same. This is what is called intertextuality. Cartoonists and readers have carefully gathered various texts on politicians and voters to see the power of ideology with the intertextuality of various other texts / images.